ETHNICITY AND RELIGION IN SOUTHWEST CHINA ([S.l.])
1 online resource.
Keywords: As China strengthens its links with its neighbours through its Belt and Road initiative, there is growing interest in the indigenous peoples of China's western and southwestern borderlands. This book, based on extensive original research, considers the indigenous peoples of Yunnan province, which is a major gateway between China and the countries of south and south-east Asia. Unlike many books on China's indigenous peoples which are written by foreigners who have lived for a while in China, this book is comprised of the work of Chinese scholars, many of them members of ethnic minorities themselves, and considers the issues from a Chinese perspective.